Reflecting on imagery: a clinical perspective and overview of the special issue of memory on mental imagery and memory in psychopathology. - Hackmann, A; Holmes, E (2004)
The authors provide an overview of the papers in the special issue of Memory on mental imagery and memory in psychopathology. The papers address emotional, intrusive mental imagery across a range of psychological disorders including post-traumatic stress disorder (PTSD), agoraphobia, body dysmorphic disorder, mood disorders, and psychosis. They include work on information processing issues including modelling cravings, conditioning, and aversions, as well as imagery qualities such as vividness and emotionality. The overview aims to place the articles in a broader context and draw out some exciting implications of this novel work. It provides a clinical context to the recent growth in this area from a cognitive behavioural therapy (CBT) perspective. We begin with PTSD, and consider links to imagery in other disorders. The clinical implications stemming from this empirical work and from autobiographical memory theory are discussed. These include consideration of a variety of techniques for eliminating troublesome imagery, and creating healthy, realistic alternatives.